Copeptin and metabolic syndrome: a systematic review - Galindo Yllu, Brenda Mireya (2022)
Background: Copeptin, a reliable marker for vasopressin release, has been associated with cardiometabolic diseases including metabolic syndrome (MetS). This systematic review aims to evaluate the association between copeptin and MetS. Methods: We searched in Pubmed, Scopus, EMBASE, and Web of Science databases until March 2021 and included observational studies (cohort studies, cross-sectional, and case-control) reporting the risk or prevalence of having MetS in patients with elevated copeptin levels compared to patients without elevated copeptin levels. Risk of bias was evaluated with the New Castle-Ottawa Scale. Meta-analysis was not performed because of the heterogeneity of the copeptin cut-off values. Results: A total of 7 studies (5 cross-sectional, 1 case-control, 1 cohort) were included comprising 11 699 participants. Most of them were performed in the adult general population. Two cross-sectional and the case-control studies found a positive significant association between higher levels of copeptin and the MetS. While three cross-sectional and the cohort study found no association. The case-control study had several methodological limitations, most cross-sectional studies where methodologically adequate and the cohort study had no methodological issues. Conclusions: The association between copeptin and MetS is inconsistent. However, this biomarker could be important for the early detection of MetS and implementation of preventive interventions. Thus, future studies should corroborate this association.